Formal Synthesis of 3-Deoxy-d-manno-Octulosonic Acid (KDO) and 3-Deoxy-d-arabino-2-heptulosonic Acid (DAH) - Pradhan, Tapan Kumar; Lin, Chun Cheng; Mong, Kwok Kong Tony (Synlett, 2013)
Practical synthetic routes to 3-deoxy-d-manno-octulosonic acid (KDO) and 3-deoxy-d-arabino-2-heptulosonic acid (DAH) from common sugar substrates are reported. Chain homologation of the sugar substrates was accomplished by Wittig olefination and Corey–Fuchs alkynylation. A new cyclization strategy was investigated to access the desired pyranosyl isomer of the KDO target.
Keywords: carbohydrates; Wittig; Corey–Fuchs; cyclization